Komunikasi Interpersonal Sebagai Peran Bawaslu Mandailing Natal Dalam Mewujudkan Pemilu Yang Luber, Jurdil - Akhiruddin Nasution; Sandy Futra; Subaidah Subaidah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The aim of this research is to provide an overview of the role of BAWASLU in realizing free and fair elections, as well as providing an analysis of how to hold a quality regional election by involving various stakeholders who have the same goal in making a fair regional election a success. This research uses the PAR method, namely Participation in Action Research, using two methods of data collection, namely observation and interviews. A total of 30 people were the subjects of the research, the 30 people were 5 BAWASLU Regency commissioners. Mandailing Natal and 25 sub-district supervisory officers spread across Mandailing Natal district. The results of this research are first, there is an effort from the BAWASLU commissioner of Mandailing Natal Regency to provide awareness to members of the sub-district supervisory committee in enforcing neutral post-conflict local election activities, so that there is an effort to continue to supervise post-conflict local election activities in a neutral manner. Second, there are monitoring and awareness efforts carried out by sub-district supervisory supervisors in providing education to always carry out neutral and balanced supervision to sub-district/village supervisory supervisors in the Mandailing Natal district.